2014
DOI: 10.1109/jmems.2014.2320509
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Ionic Liquid Ion Sources Using Arrays of Microfabricated Electrospray Emitters With Integrated Extractor Grid and Carbon Nanotube Flow Control Structures

Abstract: We report the design, fabrication, and experimental characterization of dense, monolithic, and planar arrays of externally-fed electrospray emitters with an integrated extractor grid and carbon nanotube flow control structures for low-voltage and high-throughput electrospray of the ionic liquid EMI-BF 4 in vacuum. Microfabricated arrays with as many as 1900 emitters in 1 cm 2 were fabricated and tested. Per-emitter currents as high as 5 µA in both polarities were measured, with start-up bias voltages as low as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 36 publications
(66 reference statements)
0
27
0
Order By: Relevance
“…3 and Fig. 6 shows the decrement in time period of waveform from nanoseconds to picoseconds, which indicates the improvement in throughput of FIFO design [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…3 and Fig. 6 shows the decrement in time period of waveform from nanoseconds to picoseconds, which indicates the improvement in throughput of FIFO design [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…In the condition containing both monomers and dimers, it was assumed that cations contained 85% monomers and 15% dimers and that anions contained 72% monomers and 28% dimers. 9) It was assumed that ions corresponding to 1 µA are emitted from the emitter tip. 9) The number of ions emitted from the emitter tip per second � � is described as…”
Section: Configurationmentioning
confidence: 99%
“…Based on experimental data from studies that employ EMI-BF4, the average mass-to-charge ratio at room temperature is found to be 1.5E-6 kg/C. 24 Assuming 2000 V as the applied potential, we calculate a theoretical thrust from Eq. (8) as 975 nN.…”
Section: B Design Parametersmentioning
confidence: 99%